Density, Viscosity, and Excess Properties of MDEA + H2O, DMEA + H2O, and DEEA + H2O Mixtures - Sumudu S. Karunarathne; Dag A. Eimer; Lars E. Øi (Applied Sciences, 2020)
This study presents measured density and viscosity of N-methyldiethanolamine (MDEA) + H2O, Dimethylethanolamine (DMEA) + H2O, and Diethylethanolamine (DEEA) + H2O mixtures. The density was measured at amine mass fraction w1 from 0.3 to 1 for the temperature range 293.15–353.15 K. The excess molar volumes VE were determined from density data. Redlich–Kister type polynomials were proposed to fit VE and density deviation ln(ργ) to represent measured densities. The viscosity was measured at amine mass fraction w1 from 0.3 to 1 for the temperature range 293.15–363.15 K. The viscosity deviation ηE and excess free energy of activation for viscous flow ΔGE* were determined from measured viscosities and examined for intermolecular interactions among mixture molecules. Correlations were proposed to fit viscosity data with acceptable accuracies. The McAllister’s three-body model was adopted to fit kinematic viscosities determined from density and dynamic viscosity data. The results showed the importance of examining intermolecular interactions that are discussed in McAllister’s four-body model to improve the accuracies of data fits.